Analisis Pengaruh Komponen Indeks Pembangunan Manusia Terhadap Pertumbuhan Ekonomi : Studi Panel Data 38 Kabupaten/Kota di Jawa Timur - Endang, Endang; Astuti, Hartiningsih; Tyas Udyana, Tanaya (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2024)
East Java played a strategic role in Indonesia's economy, contributing 14.6% to the national GDP with economic growth returning to 5.34% in 2022. Whilst demonstrating sound economic performance, there were significant variations in human development levels across East Java's regions. The relationship between HDI components (health, education and per capita expenditure indices) and economic growth at the regional level required further examination. Previous studies showed complex relationships between human development and economic growth; however, research analysing the specific influence of each HDI component on economic growth at the provincial level remained limited. This study analysed the impact of Human Development Index (HDI) components on economic growth in East Java, Indonesia. Using panel data from 38 districts/cities during 2018-2022, this study employed a panel data regression model with a fixed effect approach. The variables examined included the GRDP growth rate as the dependent variable, and the health index (life expectancy), education index (expected years of schooling and mean years of schooling), and per capita expenditure index as independent variables. The results showed that the health index and per capita expenditure index had positive and significant effects on economic growth, whilst the education index had a negative effect. The analysis also revealed spatial variations in the influence of HDI components on economic growth across different regions. These findings emphasised the importance of balanced investment in health, education, and living standards to promote sustainable economic growth. The research provided policy implications for the government in designing comprehensive development strategies to improve human resource quality and economic performance in East Java.